Developing visual literacy competencies while learning course content through visual journaling: teacher candidate perspectives. Issue 1 (3rd April 2019) - Loerts, Terry; Belcher, Christina
Abstract: As modes of language have changed to incorporate more robust multiliteracies, thoughtful interactions are required for teaching and learning within higher education. This qualitative case study considers how new methods of instruction are perceived in higher education through the inclusion of academic visual journals over two semesters of required literacy courses in a Bachelor of Education program in Ontario, Canada. Interviews, transcriptions of in-class dialogue, visual journal artefacts and researcher observations were used to elucidate findings which were disseminated using a Modified Constant Comparative (MCC) method of analysis. The results show how participants move from previous dependence on dominant modes of communication, such as reading and writing, to experiment with different modes of communication. Along the way, participants discover how to envision new ways of thinking about creativity, ownership, reflection and assessment. They also realize expanded communication options, who they are as learners, and the power of transmediation as reflective practice for learning deeply about course content. The results suggest that this embodied practice of academic visual journaling is significant for legitimizing new discourses surrounding visual literacy practices in higher education.